Repetitive tests of visual function improved visual acuity in young subjects - Otto, Juliane; Michelson, Georg (British Journal of Ophthalmology, 2014)
To test visual function after repetitive tests of visual acuity (VA) and contrast sensitivity (CS).Ten young female subjects performed repetitive tests of visual functions over ten sessions within 5 weeks. Per week they performed two 30 min sessions of repetitive tests of central VA, CS and vernier acuity (VT) using Michael Bach's Freiburg Vision Test FrACT 3.5.5. FrACT presents an optotype in different spatial frequencies or an optotype with decreasing contrast. Using SPSS Statistics we analysed the correlation between the number of repetitive test sessions and the change in visual function of the total group and of the individuals.After ten sessions, we found a significant improvement in VA, CS and VT. When compared with the initial session, VA increased by 32%, mean CS improved by 40% and mean VT enhanced by 47%. We also found a significant correlation between the number of test sessions and VA (r=-0.374, p<0.01), CS (r=-0.258, p<0.05) and VT (r=-0.379, p<0.01). Individual changes in vision were variable. In eight subjects, VA and CS improved significantly. VT improved in nine subjects. Our data suggest that repetitive tests of visual function may improve VA significantly.
EVALuna2:21166